A gardneri többszörös intelligencia és Franz Kett pedagógiájának metszéspontjai - Lilla SZÉNÁSI (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
Intersections between the Gardnerian Multiple Intelligence and Franz Kett’s Pedagogy. This paper focuses on possible ways of education in faith during the COVID-19 pandemic and its aftermath. During the period of online education, one could rely on the knowledge and application of Gardner’s theory of multiple intelli-gences in faith education as well, whilst the use of Kett’s pedagogy helps to ex-perience, build or rebuild, and deepen our community with God and with each other. The first part of the paper briefly outlines the concept of intelligence and then describes Howard Gardner’s theory of multiple intelligences. It gives prac-tical examples of possible ways to educate the catechumens. The second part de-scribes the emergence of Franz Kett’s pedagogy, his vision and his main con-cepts, including its starting points and methodological structure. It briefly pre-sents the floor picture as a specific method of Kett’s pedagogy. The third part summarizes the points of encounter between the Gardnerian multiple intelli-gences and Kett’s pedagogy, thus bringing into motion not only the intellectual but also the emotional intelligence.